Ecological and Environmental Disaster in Huancavelica - Pinto Herrera, Honorio (2010)
The work try to confirm, once again, that mining in Peru affects ecological systems and the environment. This is possible because of corporate power and the weakness and complicity of the state. In this sense, one of the objectives of this research is to contribute to the knowledge of a national problem, which is pollution, from a concrete case: A spill of mine tailings caudalosa Chica. The central themes developed include a description of the facts, causes, damages, penalties, environmental impunity. etc